ANALYSIS OF ROCK QUALITY AND LANDSLIDE POTENTIAL IN NORTH JERING HILLS, SLEMAN, YOGYAKARTA - Putro, Guntor Suryo; Arana, Ardhan; Huda, Alief Akbar (KURVATEK, 2024)
The study was to identify the direction and type of potential landslides, as well as assess the rock quality on the slopes of North Jering Hills. The scanline method, consisting of stretching the meter, was employed to collect data on the plane of failure. The information gathered encompassed the direction, slope level, and condition of the unsuccessful plane, aligned with the parameters in the RMR table of Bieniawski from 1989. Following the collation of data, kinematic and rock mass quality analysis was undertaken using stereographic projection and RMR parameter weighting respectively. The kinematic analysis revealed a planar avalanche type on the slope. The RMR value of the research location's slope was 80, classifying it as good rock.